Self-assembling of phenothiazine compounds investigated by small-angle X-ray scattering and electron paramagnetic resonance spectroscopy - Barbosa, Leandro R. S.; Itri, Rosangela; Caetano, Wilker [UNESP] (Amer Chemical Soc, 2008)
Small-angle X-ray scattering (SAXS) and electron paramagnetic resonance (EPR) have been carried out to investigate the structure of the self-aggregates of two phenothiazine drugs, chlorpromazine (CPZ) and trifluoperazine (TFP), in aqueous solution. In the SAXS studies, drug solutions of 20 and 60 mM, at pH 4.0 and 7.0, were investigated and the best data fittings were achieved assuming several different particle form factors with a homogeneous electron density distribution in respect to the water environment. Because of the limitation of scattering intensity in the q range above 0.15 angstrom(-1), precise determination of the aggregate shape was not possible and all of the tested models for ellipsoids, cylinders, or parallelepipeds fitted the experimental data equally well. The SAXS data allows inferring, however, that CPZ molecules might self-assemble in a basis set of an orthorhombic cell, remaining as nanocrystallites in solution. Such nanocrystals are composed of a small number of unit cells (up to 10, in c-direction), with CPZ aggregation numbers of 60-80. EPR spectra of 5- and 16-doxyl stearic acids bound to the aggregates were analyzed through simulation, and the dynamic and magnetic parameters were obtained. The phenothiazine concentration in EPR experiments was in the range of 5-60 mM. Critical aggregation concentration of TFP is lower than that for CPZ, consistent with a higher hydrophobicity of TFP. At acidic pH 4.0 a significant residual motion of the nitroxide relative to the aggregate is observed, and the EPR spectra and corresponding parameters are similar to those reported for aqueous surfactant micelles. However, at pH 6.5 a significant motional restriction is observed, and the nitroxide rotational correlation times correlate very well with those estimated for the whole aggregated particle from SAXS data. This implies that the aggregate is densely packed at this pH and that the nitroxide is tightly bound to it producing a strongly immobilized EPR spectrum. Besides that, at pH 6.5 the differences in motional restriction observed between 5- and 16-DSA are small, which is different from that observed for aqueous surfactant micelles.